Eletroforese das proteínas séricas e urinárias de cães com erliquiose na fase aguda - Contin, Catarina Micali [UNESP] (2015)
Canine ehrlichiosis is one of the most frequent haemoparasitosis between domestic dogs and has high prevalence in tropical regions. Despite the innumerous investigations and progresses in the pathogenesis comprehension and diagnosis of the disease, little is known on the glomerulo-tubular alterations of dogs stricken by ehrlichiosis. The aim of this study was to associate the electrophoretic profile of blood and urinary proteins with the possible glomerulo-tubular alterations found in dogs with acute-phase ehrlichiosis. The Control Group (CG) was formed by 18 healthy dogs and the Sick Group (SG), by 24 animals, both groups with unspecified genders, races and ages. The experimental protocol included assessment of the dogs' clinical conditions, and regarding the sick ones, based on the clinical signs and the presence of morula in the ear-tip blood smears. From the animals of both groups, peripheral blood and urine samples were obtained for protein electrophoretical analysis through the polyacrylamide gel with dodecyl sodium sulfate (SDS-PAGE) electrophoresis technique. Eleven protein fractions were selected in the blood sera densitometry trace, with molecular weights ranging from 23 to 123 kDa (kilodaltons). The results showed that some acute-phase proteins change in dogs with acute-phase ehrlichiosis. Significant difference between the studied groups was observed in serum concentrations of transferrin, haptoglobin, IgG (light chain) and albumin, the latter with lower levels in the Sick Group. The electophoretical analysis of urine showed a larger number of protein fractions excreted by dogs with acute-phase ehrlichiosis (295), when in comparison with the ones in the CG (174). High (>60 kDa) and low (<60 kDa) molecular weight proteins were found in the sick dogs' urine, suggesting that the disease in its acute phase causes lesions in both glomeruli and tubules, respectively